PENGGUNAAN MEDIA AUDIO-VISUAL BERBASIS TEKNOLOGI DALAM PEMBELAJARAN BAHASA INDONESIA DI SD - Putri Hana Pebriana; Aulia Utamy; Dina Olyvia; Rizky Eka Putri; Nurhasanah Syahrani Situmorang; Sabri Januarti; Ghitsa Nurunnisa; Muhammad Sholeh Andreansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Indonesian learning in elementary schools has a strategic role in developing students' language skills which include listening, speaking, reading, and writing. However, the learning process in the classroom is often still dominated by conventional methods that are centered on teachers, resulting in low interest and active participation of students. Along with the development of educational technology, the use of technology-based audio-visual media is one of the effective alternatives to improve the quality of Indonesian learning. Audio-visual media is able to present learning materials in a concrete way through the combination of sound elements and moving images, making it easier for students to understand concepts, enrich vocabulary, and improve imagination and language skills. This article aims to examine the role and benefits of the use of technology-based audio-visual media in Indonesian language learning in elementary schools. Methods used